Kepatuhan Wajib Pajak Kendaraan Bermotor Mahasiswa di DKI Jakarta Dipengaruhi oleh Kesadaran Pembayaran dan Sanksi Perpajakan - Atmojo, Tirza Naftali; Sandra, Amelia (Global Research on Economy, Business, Communication, and Information, 2024)
Regional tax is a mandatory contribution to the region that is owed by individuals or entities that are coercive in nature. This research aims to examine the influence of payment awareness, tax sanctions, and digitalization of the regional tax system on taxpayer compliance of DKI Jakarta students. The hypothesis in this research is that the variables of payment awareness, tax sanctions, and digitalization of the regional tax system have a positive effect on taxpayer compliance of DKI Jakarta students. The results of the tests that have been carried out show that the independent variable has a significance level of 5%. Based on the results obtained from the F test, it has a Sig value. 0.000, from the t test it was found that the payment awareness variable had sig. of 0.002, the tax sanctions variable has sig. of 0.0085, and the digitalization variable has a sig value. of 0.2245. The conclusion from the research and testing that has been carried out is that awareness of payments and tax sanctions has sufficient evidence to have a positive effect on taxpayer compliance. Digitalization of the regional tax system has not been proven to have a positive effect on taxpayer compliance.